Strategic plan for R.T. Lapena Enterprise - Arano, Nichelle Gay U. (School of Management, University of the Philippines Mindanao, 2010)
R.T. Lapeña Enterprises is a sole proprietorship engaged in renting out of commercial buildings and taxis. With its management's quest for operational expansion and higher profitability, a new project was developed. During the operational stage of the new project, losses were incurred. R.T. Lapeña Enterprises was not able to hit its sales target for the project. Interested renters and prospective locators seem to have that "wait & see attitude". Since the project was considered as a major project of the enterprise, this study was more focused on the said project. This strategic planning paper was prepared precisely to address problems arising from the commercial buildings leasing operation of R.T. Lapeña Enterprises. The study highlights the proposed strategies for the achievement of the real estate operations goals of R.T. Lapeña Enterprises. Guided by the strategic planning framework, an analysis of the external environment was conducted. The evaluation resulted to the identification of the following opportunities: (a) Davao City is a major tourist destination in the region; (b) the healthy economy of Davao City; and (c) fast growing populace of the City. The following environmental threats were detected: (a) stiff competition; (b) political instability; and (c) high inflation rate. To be able to identify the key strengths and weaknesses of the enterprise; an analysis of its internal environment was also conducted. The following were identified strengths of the enterprise: (a) R.T. Lapeña Enterprises was the first to offer a one stop shop destination in the immediate vicinity of the Davao City International Airport and (b) it has land properties in the immediate vicinity of the Airport that can be developed. The weaknesses identified were the following: (a) inefficient operational performance; (b) land left barren for decades; (c) no manual of operations and unarticulated organizational goals; (d) no internal marketing force; and (e) job descriptions for each position was not defined. To prepare the strategic plan for the course of its real estate operations; several strategies were being generated through the SWOT Matrix Analysis. Strategies to be pursued were logically ordered by using the Quantitative Strategic Planning Matrix, They were as follows: (a) to boost market potential through positioning and differentiation; (b) to overcome competition by imposing a low-costing strategy and by strengthening organizational capacity; (c) to improve market efficiency by enhancing the new project?s amenities and features an maximizing the use of resources; (d) to sell properties and invest in other worthwhile investments when operational losses continue up to 5 years of operations. To ensure the success of the endeavor, evaluation of performance is to be gauge through Key Result Areas and Performance Indicators.